Prophylactic Catechin-Rich Green Tea Extract Treatment Ameliorates Pathogenic Enterotoxic Escherichia coli-Induced Colitis - Jeong-Won Kim; Chang-Yeop Kim; Jin-Hwa Kim; Ji-Soo Jeong; Je-Oh Lim; Je-Won Ko; Tae-Won Kim (Pathogens, 2021)
In this study, we explored the potential beneficial effects of green tea extract (GTE) in a pathogenic Escherichia coli (F18:LT:STa:Stx2e)-induced colitis model. The GTE was standardized with catechin and epigallocatechin-3-gallate content using chromatography analysis. Ten consecutive days of GTE (500 and 1000 mg/kg) oral administration was followed by 3 days of a pathogenic E. coli challenge (1 × 109 CFU/mL). In vitro antibacterial analysis showed that GTE successfully inhibited the growth of pathogenic E. coli, demonstrating over a 3-fold reduction under time- and concentration-dependent conditions. The in vivo antibacterial effect of GTE was confirmed, with an inhibition rate of approximately 90% when compared to that of the E. coli alone group. GTE treatment improved pathogenic E. coli-induced intestinal injury with well-preserved epithelial linings and villi. In addition, the increased expression of annexin A1 in GTE-treated jejunum tissue was detected, which was accompanied by suppressed inflammation-related signal expression, including TNFA, COX-2, and iNOS. Moreover, proliferation-related signals such as PCNA, CD44, and Ki-67 were enhanced in the GTE group compared to those in the E. coli alone group. Taken together, these results indicate that GTE has an antibacterial activity against pathogenic E. coli and ameliorates pathogenic E. coli-induced intestinal damage by modulating inflammation and epithelial cell proliferation.